Response of Cashew to Drip Irrigation and Mulching in Coastal Orissa - P. C. Pradhan; J. N. Mishra; J.C. Paul (Journal of Soil and Water Conservation, 2022)
Experiments were conducted in the farmers’ field on the loamy soil in coastal Orissa for two consecutive years (2005-07), to evaluate the economic feasibility of drip irrigation with black LDPE mulch in a cashew crop planted during July 2000. Actual evapotranspiration for cashew crop was estimated using pan Evaporation method. The net irrigation volume (V) was determined after deducting the effective rainfall. The net average seasonal water requirement of crop was estimated to be 997 mm. The effect of three irrigation levels viz. V, 0.8 V and 0.6 V with drip in conjunction with black LDPE mulch were studied on biometric and yield response of cashew crop. The results of ring basin surface irrigation either alone or in conjunction with black LDPE mulch were compared with drip irrigation. The study indicated that, better plant growth, more number of flowers per panicle and enhancement in the yield under drip irrigation with plastic mulch. The highest nut yield (1.42 t/ha) was recorded under 0.8 V drip irrigation with mulch (T6) as compared to other treatments. An increase of 108 % in nut yield and 122 % in net seasonal income were recorded in case of 0.8V drip irrigation with mulch as compared to conventional ring basin irrigation. The benefit cost ratio was also found to be highest (3.1) for the same treatment. Mulch alone could increase the yield by 16% even in the absence of drip.